Translation and Semantic Shift of Islamic Vocabulary in English Abstracts: A Corpus-Based Study at an Indonesian Islamic University - Jamal, Misbahuddin; Simbuka, Srifani (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
Incorporating Nation’s vocabulary classification, this study investigates the translation and semantic shifts of Islam-related vocabulary in the abstracts of undergraduate and postgraduate theses. A corpus of 810 English and Bahasa Indonesia abstracts, sampled from a total of 1,928, was analyzed using Antwordprofiler and Antconc software. Findings indicate that translation strategies employed include phonetic alteration, pure borrowing, and one-to-one translation. Specifically, loanwords of Arabic origin were predominantly translated using pure borrowing, with some phonetic and/or orthographic modification in both Bahasa Indonesia and English. The translated vocabulary primarily consisted of Arabic-origin words with Bahasa Indonesia orthographic adaptations rather than their original Arabic forms. Additionally, semantic shifts were observed in the adoption of Islam-related Arabic vocabulary into Bahasa Indonesia. This is attributed to 1) the introduction of Quranic meanings, often differing from the common understanding of Arabic words at the time of the Quran’s revelation, and 2) modifications to accommodate the traditions of Indonesian local Muslim communities. The implications of this study highlight the need for translators to be aware of the cultural and religious contexts that influence semantic shifts. Moreover, this research underscores the importance of understanding the dynamic nature of language in the context of religious texts, which can lead to more accurate and culturally sensitive translations.